2017
DOI: 10.1016/j.bbadis.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of glial markers, chemokines, and opioid receptors in the spinal cord of type 2 diabetic monkeys

Abstract: Neuroinflammation is a pathological condition that underlies diabetes and affects sensory processing. Given the high prevalence of pain in diabetic patients and crosstalk between chemokines and opioids, it is pivotal to know whether neuroinflammation-associated mediators are dysregulated in the central nervous system of diabetic primates. Therefore, the aim of this study was to investigate whether mRNA expression levels of glial markers, chemokines, and opioid receptors are altered in the spinal cord and thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 60 publications
5
21
0
Order By: Relevance
“…In animal models of diabetes mellitus (DM), high blood glucose has been shown to reduce the effectiveness of opioid receptor agonists [14][15][16]. Studies on relevant mechanisms have shown that high blood glucose is associated with changes in the expression of opioid receptor genes [17,18], the body's metabolism [9], and neurotransmitter levels [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of diabetes mellitus (DM), high blood glucose has been shown to reduce the effectiveness of opioid receptor agonists [14][15][16]. Studies on relevant mechanisms have shown that high blood glucose is associated with changes in the expression of opioid receptor genes [17,18], the body's metabolism [9], and neurotransmitter levels [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…CCR4, CCR6, CCR8, CCR10, CXCR3, CXCR5, and CXCR6) are simultaneously upregulated . In addition, mRNA expression levels of classical opioid receptor subtypes μ, κ, and δ are downregulated . These findings demonstrate that there is potential cross‐talk between chemokines and opioids in the spinal cord of diabetic monkeys .…”
Section: Introductionmentioning
confidence: 77%
“…In addition, mRNA expression levels of classical opioid receptor subtypes μ, κ, and δ are downregulated . These findings demonstrate that there is potential cross‐talk between chemokines and opioids in the spinal cord of diabetic monkeys . However, potential changes in other ligand–receptor systems associated with neuroinflammation in primates with T2DM are virtually unknown.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations